2005
DOI: 10.4319/lom.2005.3.101
|View full text |Cite|
|
Sign up to set email alerts
|

Theoretical and empirical conversion factors for determining bacterial production in freshwater sediments via leucine incorporation

Abstract: Bacteria play an extraordinarily important role in carbon transformations. It is therefore crucial to accurately measure bacterial production. One of the most widely used methods is the leucine method. From rates of leucine incorporation bacterial carbon production can be derived by empirical or theoretical conversion factors (CFs). However, only few empirical CFs have been established, and no estimation of the theoretical conversion factor for freshwater systems exists until today. Therefore, we determined bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 29 publications
3
30
0
Order By: Relevance
“…It has been reported that differences in leucinebased estimates of BP may be driven in part by variation in the in the efficiency with which leucine is converted into bacterial biomass and that the use of a constant leucine-to-CCF may inaccurately represent in situ rates of BP and BGE (Kirchman, 1993;Buesing and Marxsen, 2005;Alonso-Sáez et al, 2007). Although the influence of variability in CCF may be most pronounced in oligotrophic waters (Alonso-Sáez et al, 2007), this phenomenon may be applicable to any range of systems differing in productivity or degree of resource enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that differences in leucinebased estimates of BP may be driven in part by variation in the in the efficiency with which leucine is converted into bacterial biomass and that the use of a constant leucine-to-CCF may inaccurately represent in situ rates of BP and BGE (Kirchman, 1993;Buesing and Marxsen, 2005;Alonso-Sáez et al, 2007). Although the influence of variability in CCF may be most pronounced in oligotrophic waters (Alonso-Sáez et al, 2007), this phenomenon may be applicable to any range of systems differing in productivity or degree of resource enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…Cell production, in turn, was calculated from biomass production of prokaryotes (i.e., [ 3 H]leucine incorporation), assuming that 1 m 3 of prokaryotic biomass equaled 7.8 fg of C and that the volume of the average cell in water samples was 0.02 m 3 (8). Biomass production was calculated from leucine incorporation rates using a conversion factor established for freshwater sediment bacteria (12). Isotope dilution has been found to be minor (1.17) (10) and was therefore not taken into account.…”
Section: Methodsmentioning
confidence: 99%
“…Fungal biomass, growth rate, and production were estimated by determining ergosterol concentrations and rates of [ 14 C]acetate incorporation into ergosterol (28). Samples were incubated for 5 h at ambient lake temperatures in 4 ml of filtered lake water containing sodium [ 14 C]acetate (Amersham, Little Chalfont, Buckinghamshire, United Kingdom); the specific activity of added acetate was 3.7 10 7 Bq mmol Ϫ1 (27). The total added acetate concentration was 5 mM.…”
Section: Vol 72 2006 Benthic Microbial Productivity 597mentioning
confidence: 99%